The Effect of Collectivism on Union Attitudes and Beliefs - Beadles, II, Nicholas; Lowery, Christopher; Wilhau, Aric (Journal of Applied Business and Economics, 2023)
Researchers have attempted to understand the unionization process by examining the variables surrounding an individual’s decision to vote for a union. Despite the linkage of an individual’s attitude towards unions and the individual’s propensity to vote for a union, there has been little research which attempts to understand which personality constructs might be predictive of general attitudes towards unions. Using causal modeling techniques, we investigated the effect of collectivism on general union attitudes and union instrumentality beliefs with a sample of workers from the Southeastern United States. It was found that a more collectivist orientation is positively associated with beliefs about, and feelings towards, unions. Ancillary analyses revealed that African Americans held greater union favorability attitudes and greater positive beliefs about union instrumentality relative to Caucasians, though a more collectivist nature among African Americans did not explain these findings. It was also revealed that females had a more positive general attitude towards unions and were marginally more positive regarding the effects of unions on specific issues as compared to males.